Molecular Characterization of Irreversible Pulpitis: A Protocol Proposal and Preliminary Data - Fouad, Ashraf F. (Frontiers in Dental Medicine, 2022)
Introduction: An attempt to determine the association of a large array of inflammatory proteins in pulpitis with precise measurement of clinical signs and symptoms, and to correlate these findings with levels in peripheral blood has not been reported. Such an analysis could serve to identify key clinical findings and potential biomarkers to predict the prognosis of vital pulp therapy. The aim of this study was to undertake a preliminary, proof-of-concept study to correlate the levels of key inflammatory mediators in cariously exposed dental pulp of adults with reversible or irreversible pulpitis, and no apical periodontitis, with a panel of subjective and objective diagnostic clinical findings as well as the status of the pulp upon exposure. Pulpal and peripheral blood inflammatory mediators were also compared. Methods: Dental pulp and peripheral blood were sampled. The Luminex technology was used to assess the expression of a panel of 45 inflammatory proteins to determine their association with clinical signs and symptoms of reversible or irreversible pulpitis. Results: Data from three pulpal and three peripheral blood samples were used for the analysis. The correlation of levels of the 45 proteins in the inflamed dental pulp and peripheral blood was 0.87. The pulp had significantly higher levels of these proteins collectively than peripheral blood (t-test, p=0.047). The following proteins had correlated at a level of ≥ 0.8 with the duration of pain with cold: MMP-12, MMP-9, RANTES, MIP-2, MCP-1, MMP-2, MMP-1 and P-Selectin. Relatively high correlations (0.5 – 0.75) were also present between these proteins and presenting pain level. Conclusions: Several pulpal proteins correlated well with spontaneous and evoked pain parameters. Peripheral blood may not be necessary in future similar studies. Finally, additional data is needed to identify candidate proteins to be investigated as potential markers of truly irreversible pulp inflammation.